ANALYSIS OF ECONOMIC GROWTH AND EXPORT DEVELOPMENT OF BANGKA BELITUNG ISLANDS - Jufri Sani Akbar; Nadia Sri Rezeki (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Economic growth is one indicator to measure that an area is prosperous and prosperous, while exports are one of the efforts to increase economic growth. Indonesia's economic growth in Quarter III-2021 grew by 3.51 percent when compared to Quarter III-2020 (y-on-y), and the development of Indonesia's export value in September 2021 reached US$ 20.60 billion, down 3.84 percent compared to exports in August 2021. With national conditions that will affect regional economic growth, the Bangka Belitung Islands Province's economic growth rate at the end of 2020 has decreased by negative 2.30% and the value of nomigas exports is negative 8.96%. By using a regression analysis tool, it is found that economic growth for the 12 quarters of the period 2018 to 2020 is positively correlated with export developments, which is 0.247 positive. The correlation value is in the low or weak category. Meanwhile, the effect of exports on economic growth is 0.061 or 6.1%. Efforts to increase economic growth can apply the theory of economic growth, implement strategies to increase exports, because there is a strength possessed by the Province of the Bangka Belitung Islands in the form of production factors. Keywords: Economic Growth and Export Development.